Parametric Study of Experimental and CFD Simulation Based Hydrodynamics and Mass Transfer of Rotating Packed Bed: A Review - Zahir, Abdul; Kumar, Perumal; Saptoro, Agus; Shah, Milin; Tiong, Angnes Ngieng Tze; Hameed, S. (2023)
The emission of CO2 into the atmosphere is one of the major causes of the greenhouse effect, which has a devastating effect on the environment and human health. Therefore, the reduction of CO2 emission in high concentration is essential. The Rotating Packed Bed (RPB) reactor has gained a lot of attention in post-combustion CO2 capture due to its excellent rate of mass transfer and capture efficiency. To better understand the mechanisms underlying the process and ensure optimal design of RPB for CO2 absorption, elucidating its hydrodynamics is of paramount importance. Experimental investigations have been made in the past to study the hydrodynamics of RPB using advanced imaging and instrumental setups such as sensors and actuators. The employments of such instruments are still challenging due to the difficulties in their installation and placement in the RPB owing to the complex engineering design of the RPB. The hydrodynamics of the RPB can be affected by various operational parameters. However, all of them cannot be evaluated using a single instrumental setup. Therefore, the experimental setups generally result in a partial understanding of the flow behavior in the RPB. The cons and pros of experimental methods are reported and critically discussed in this paper. Computational Fluid Dynamics (CFD), on the other hand, is a powerful tool to visually understand the insights of the flow behavior in the RPB with accurate prediction. Moreover, the different multiphase and turbulence models employed to study the hydrodynamics of RPB have also been reviewed in-depth along with the advantages and disadvantages of each model. The models such as Sliding Mesh Model (SMM) and rotating reference frame model have been adopted for investigating the hydrodynamics of the RPB. The current research gaps and future research recommendations are also presented in this paper which can contribute to fill the existing gap for the CFD analysis of Rotating Packed Bed (RPB) for CO2 absorption.